(untitled) (FULafia Journal of Science and Technology, 2018)
Environmental and hygienic concerns associated with traditional fish smoking structures restrict the sale and consumption of smoked products to local markets. This study evaluated the performance of three(improved kiln oven (IKO), mud-type ovens (MTO) and extended drum ovens (EDO)) locally available Biofuelledfish smoking structures and proposed modifications to improve product quality.Three groups of prepared freshwater catfish (Clarias gariepinus) with average live weights of 1.93 kg±46 g, 1.92 kg±50 g and 1.86 kg±50 g was used as test samples. Smoking profiles, final moisture content (FMC), smoking time, smoking temperatures, percentage weight loss (WL) and organoleptic evaluation (ORE) were the performance indicators used during evaluation